Social Franchising and a Nationwide Mass Media Campaign Increased the Prevalence of Adequate Complementary Feeding in Vietnam: A Cluster-Randomized Program Evaluation. Issue 4 (8th February 2017) - Rawat, Rahul; Nguyen, Phuong Hong; Tran, Lan Mai; Hajeebhoy, Nemat; Nguyen, Huan Van; Baker, Jean; Frongillo, Edward A; Ruel, Marie T; Menon, Purnima
Abstract: Background: Rigorous evaluations of health system–based interventions in large-scale programs to improve complementary feeding (CF) practices are limited. Alive & Thrive applied principles of social franchising within the government health system in Vietnam to improve the quality of interpersonal counseling (IPC) for infant and young child feeding combined with a national mass media (MM) campaign and community mobilization (CM). Objective: We evaluated the impact of enhanced IPC + MM + CM (intensive) compared with standard IPC + less-intensive MM and CM (nonintensive) on CF practices and anthropometric indicators. Methods: A cluster-randomized, nonblinded evaluation design with cross-sectional surveys ( n = ∼500 children aged 6–23.9 mo and ∼1000 children aged 24–59.9 mo/group) implemented at baseline (2010) and endline (2014) was used. Difference-in-difference estimates (DDEs) of impact were calculated for intent-to-treat (ITT) analyses and modified per-protocol analyses (MPAs; mothers who attended the social franchising at least once: 62%). Results: Groups were similar at baseline. In ITT analyses, there were no significant differences between groups in changes in CF practices over time. In the MPAs, greater improvements in the intensive than in the nonintensive group were seen for minimum dietary diversity [DDE: 6.4 percentage points (pps); P < 0.05] and minimum acceptable diet (8.0 pps; P < 0.05). Significant stunting declines occurred in both intensive (7.1 pps) and nonintensive (5.4 pps) groups among children aged 24–59.9 mo, with no differential decline. Conclusions: When combined with MM and CM, an at-scale social franchising approach to improve IPC, delivered through the existing health care system, significantly improved CF practices, but not child growth, among mothers who used counseling services at least once. A greater impact may be achieved with strategies designed to increase service utilization. This trial was registered at clinicaltrials.gov as NCT01676623.